Penerapan Keselamatan Radiasi Sinar X pada Petugas Radiasi di Instalasi Radiologi - Syahroni Lubis; Edwin Suharlim; Inta Masita Hayati; Mila Aulia Hamidah; Adhitya Pratama (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
The use of X-rays in radiology installations plays a crucial role in medical diagnosis. However, X-rays are a form of ionizing radiation that can pose serious health risks if exposure to medical personnel is not properly controlled. This study aims to evaluate the implementation of X-ray radiation safety measures for radiology workers through a literature review. The method used is a literature review of 10 scientific both from domestic and international sources, which discuss the implementation of radiation protection in radiology facilities. The review results show that most facilities have applied the ALARA principle (As Low As Reasonably Achievable), with a 76% rate of personal protective equipment (PPE) usage, 60% performing regular dose monitoring, and only 40% regularly conducting radiation protection training. Additionally, compliance with standard operating procedures (SOPs) was recorded at 72%, while only 30% of facilities had active survey meters. These findings indicate that challenges remain in the comprehensive implementation of radiation safety. Therefore, enhanced education, supervision, and availability of protective facilities are needed to ensure the occupational safety of radiation workers in radiology departments